Unit Cost Comparison Method Using Activity-Based Costing of Appendectomy Against INA-CBG's Rates in Bhayangkara Hospital Medan 2018 - Jimy Fran; Destanul Aulia; Juanita Juanita (Britain International for Academic Research (BIAR) Publisher, 2020)
Determination of tariffs with traditional methods is considered unable to overcome various difficulties in determining rates in hospitals. Activity-Based Costing (ABC) is one method of calculating rates that are considered efficient. The purpose of this study was to determine the ratio of unit cost to INA-CBG's rates in class III acute appendicitis patients at Bhayangkara Medan Secondary Hospital in 2018. This study is a quantitative descriptive study using the ABC method, where this study calculates the unit cost of acute appendicitis. Samples were taken based on total sampling technique, that is, all patients with class III acute appendicitis in Bhayangkara Hospital Medan. Data was collected using primary data in the form of direct interviews from the field and secondary data in the form of patient medical records, as well as costs incurred from all activities that happened. Analysis of the data used in this study is a non-statistical quantitative analysis test. The results of the study show that the unit cost is smaller than the INA-CBG's rate with a difference of Rp. 1,699,448.00. It is recommended that the Head of the Bhayangakara Level II Hospital in Medan analyze the unit cost of each disease using the ABC method in order to have efficient tariffs.